CONDUCTIVITIES OF BROMAMINE- TIN WATER AND METHANOL AT VARlO US TEMPERATURES (Biological Sciences - PJSIR, 2022)
The ionic conductivity of bromamine- T (BAT) in water and methanol as solvent has been studied as a function oftemperature. The conductance data have been analysed by the Debye-Huckel, Fuosskraus, Shedlovsky and FuossAccascina Equations. The energy of activation of the rate process, thermodynamic parameters, molar conductivity atinfinite dilution (AO ), Walden constant, dissociation and association constants (1